The Quranic ʾAbb as a South Arabian magical formula - Atbuosh, Mohammed (Proceedings of the Seminar for Arabian Studies, 2024)
This article proposes a new interpretation for the common magical formula in the Ancient South Arabian inscriptions “Wd-ʾb”, which is usually translated as (Wadd is father). Instead, it suggests interpreting it as "Wadd blessing" based on the Semitic root "ʾb," which also appears as the problematic Qurʾānic term “ʾabbā” and in various Yemeni dialects (ʾab; ʾabīb) meaning (grass, fodder). The custom of engraving similar protection formulas on the building may have survived in Yemen and other regions, through engraving Islamic blessing formulas such as mā šāʾ Allāh (what God has willed) or tabārak Allāh (what God has blessed), which is quite common in modern Yemen.